Encapsulation of collagen mimetic peptide-tethered vancomycin liposomes in collagen-based scaffolds for infection control in wounds - Thapa, Raj Kumar (Acta Biomater, 2019)
Wound infections are a significant clinical problem affecting millions of people worldwide. Topically applied antibacterial formulations with longer residence time and controlled antimicrobial release would offer significant benefits for improved prevention and treatment of infected wounds. In this study, we developed collagen mimetic peptide (CMP) tethered vancomycin (Van)-containing liposomes (Lipo) (CMP-Van-Lipo) hybridized to collagen-based hydrogels („co-gels,‟ e.g., collagen/fibrin combination hydrogels) for the treatment of methicillin-resistant Staphylococcus aureus (MRSA) infections in vitro and in vivo. Tethering CMP-Van-Lipo nanostructures to co-gels enabled sustained Van release and enhanced in vitro antibacterial effects against MRSA as compared to Van loaded co-gels or Van-Lipo loaded co-gels following multiple fresh bacterial inoculations over a period of 48 h. These results were successfully translated in vivo wherein MRSA infected wounds were effectively treated with CMP-Van-Lipo loaded co-gels up to 9 days, whereas the activity of Van loaded co-gels and Van-Lipo loaded co-gels were limited to < 2 days. Moreover, CMP-Van-Lipo retained in vivo antibacterial activity even after re-inoculation with bacteria; however, Van loaded co-gels and Van-Lipo loaded co-gels allowed significant bacterial growth resonating their limited efficacy. Altogether, these results provide proof-of-concept that CMP-Van-Lipo loaded co-gels can be effective topical formulations for preventative treatment of MRSA wound infections.